Carbon stock of oil palm plantations and tropical forests in Malaysia: A review - Kho, Lip Khoon; Jepsen, Martin Rudbeck (Singapore journal of tropical geography, 2015)
In Malaysia, the main land change process is the establishment of oil palm plantations on logged‐over forests and areas used for shifting cultivation, which is the traditional farming system. While standing carbon stocks of old‐growth forest have been the focus of many studies, this is less the case for Malaysian fallow systems and oil palm plantations. Here, we collate and analyse Malaysian datasets on total carbon stocks for both above‐ and below‐ground biomass. We review the current knowledge on standing carbon stocks of 1) different forest ecosystems, 2) areas subject to shifting cultivation (fallow forests) and 3) oil palm plantations. The forest ecosystems are classified by successional stage and edaphic conditions and represent samples along a forest succession continuum spanning pioneer species in shifting cultivation fallows to climax vegetation in old‐growth forests. Total carbon stocks in tropical forests range from 4 to 384 Mg C/ha, significantly wider than the range of total carbon stocks of oil palm plantations, 2 to 60 Mg C/ha. Conversion of old‐growth forest areas to oil palm plantations leads to substantial reduction in carbon storage, while conversion of forest fallows to oil palm plantations may sustain or even increase the standing carbon stock.